Hubungan Penggunaan Pestisida Terhadap Kejadian Hipertensi Pada Petani Sayur mayur Di Wilayah Puskesmas Sambirejo Kabupaten Rejang Lebong Tahun 2021 - Almaini Almaini; Mulyadi Mulyadi; Yanti Sutriyanti; Chandra Buana (Poltekkes Kemenkes Bengkulu, 2022)
Hypertension is called the silent killer because it is often without complaints, so the patient does not know he has hypertension and is only known after complications occur. The estimated number of hypertension cases in Indonesia is 63,309,620 people, while the death rate in Indonesia due to hypertension is 427,218 deaths. Exposure to pesticides in the long term can cause chronic poisoning in humans so that it can cause various health impacts on the community, especially farmers who use pesticides, one of which is hypertension which can occur during acute or chronic exposure. on vegetable farmers in the area of ​​Sambirejo Public Health Center, Rejang Lebong Regency. The research method used a cross-sectional study approach (cross-sectional study), the sampling was carried out by simple random sampling with a sample of 52 people. The results of the bivariate statistical analysis showed a significant relationship between length of time being a farmer p=0.019, OR=2.98, and the combination of pesticide use p=0.001 OR=9.9 with the incidence of hypertension. The results of the multivariate analysis found that length of time being a farmer was the dominant factor in influencing the incidence of hypertension in vegetable farmers in the Sambirejo Health Center area, p = 0.019, OR = 2.098. The conclusion is that there is a statistically significant relationship between length of time being a farmer and the incidence of hypertension in vegetable farmers in the Sambirejo Health Center area. It is suggested that further research is needed to obtain cohort data.